Cost of elective percutaneous coronary intervention in Malaysia: a multicentre cross-sectional costing study. Issue 5 (28th May 2017) - Lee, Kun Yun; Ong, Tiong Kiam; Low, Ee Vien; Liow, Siow Yen; Anchah, Lawrence; Hamzah, Syuhada; Liew, Houng Bang; Ali, Rosli Mohd; Ismail, Omar; Ahmad, Wan Azman Wan; Said, Mas Ayu; Dahlui, Maznah
Abstract : Objectives: Limitations in the quality and access of cost data from low-income and middle-income countries constrain the implementation of economic evaluations. With the increasing prevalence of coronary artery disease in Malaysia, cost information is vital for cardiac service expansion. We aim to calculate the hospitalisation cost of percutaneous coronary intervention (PCI), using a data collection method customised to local setting of limited data availability. Design: This is a cross-sectional costing study from the perspective of healthcare providers, using top-down approach, from January to June 2014. Cost items under each unit of analysis involved in the provision of PCI service were identified, valuated and calculated to produce unit cost estimates. Setting: Five public cardiac centres participated. All the centres provide full-fledged cardiology services. They are also the tertiary referral centres of their respective regions. Participants: The cost was calculated for elective PCI procedure in each centre. PCI conducted for urgent/emergent indication or for patients with shock and haemodynamic instability were excluded. Primary and secondary outcome measures: The outcome measures of interest were the unit costs at the two units of analysis, namely cardiac ward admission and cardiac catheterisation utilisation, which made up the total hospitalisation cost. Results: The average hospitalisation cost ranged between RM11 471 (US$3186) and RM14 465 (US$4018). PCI consumables were the dominant cost item at all centres. The centre with daycare establishment recorded the lowest admission cost and total hospitalisation cost. Conclusions: Comprehensive results from all centres enable comparison at the levels of cost items, unit of analysis and total costs. This generates important information on cost variations between centres, thus providing valuable guidance for service planning. Alternative procurement practices for PCI consumables may deliver cost reduction. For countries with limited data availability, costing method tailored based on country setting can be used for the purpose of economic evaluations. Registration: Malaysian MOH Medical Research and Ethics Committee (ID: NMRR-13-1403-18234 IIR).